Diagnosis, grading, and treatment recommendations for children, adolescents, and young adults with sinusoidal obstructive syndrome: an international expert position statement. Issue 1 (January 2020) - Mahadeo, Kris M; Bajwa, Rajinder; Abdel-Azim, Hisham; Lehmann, Leslie E; Duncan, Christine; Zantek, Nicole; Vittorio, Jennifer; Angelo, Joseph; McArthur, Jennifer; Schadler, Keri; Chan, Sherwin; Tewari, Priti; et al.
Summary: Sinusoidal obstructive syndrome, also known as hepatic veno-occlusive disease, is a potentially life-threatening complication that occurs in children undergoing haemopoietic stem-cell transplantation (HSCT). Differences in the incidence of genetic predisposition and clinical presentation of sinusoidal obstructive syndrome between children and adults have rendered the historical Baltimore and Seattle diagnostic criteria insufficient for children. In 2017, the European Society for Blood and Marrow Transplantation (EBMT) proposed the first paediatric diagnostic and severity grading guidelines for sinusoidal obstructive syndrome, intended for implementation across European centres. However, universally accepted paediatric criteria are needed to ensure prompt diagnosis, definitive treatment, and improved outcomes for children, adolescents, and young adults with sinusoidal obstructive syndrome, and to facilitate international clinical research collaboration. We convened an international panel of multidisciplinary experts including physicians with expertise in HSCT, paediatric intensive care, nephrology, hepatology, radiology, pathology, and transfusion medicine; HSCT advanced-practice providers and medical trainees; pharmacists; and translational and basic science researchers from the Pediatric Acute Lung Injury and Sepsis Investigators Network, the EBMT, the Pediatric Blood and Marrow Transplant Consortia, and several other institutions with extensive experience in sinusoidal obstructive syndrome. Panellists convened at The University of Texas, MD Anderson Cancer Center (Houston, TX, USA) in February, 2019, to evaluate the available evidence. In this expert position statement paper, we provide consensus recommendations for the international implementation of guidelines for the diagnosis, severity grading, and treatment of sinusoidal obstructive syndrome among children, adolescents, and young adults. We endorse universal adoption of paediatric diagnostic guidelines for sinusoidal obstruction syndrome as proposed by the EBMT, and provide implementation guidance for standardisation across centres; we have further proposed adjunctive use of age-appropriate organ-specific toxicity criteria for severity grading and provided prophylaxis and treatment considerations among children and adolescent and young adult patients. Key recommendations include: (1) liver biopsy, portal venous wedge pressure, and reversal of portal venous flow on Doppler ultrasonography should not be used for the routine diagnosis of sinusoidal obstructive syndrome in children, adolescents, and young adults; (2) platelet refractoriness can be defined as a corrected count increment of less than 5000–7500 following at least two sequential ABO-compatible fresh platelet transfusions; (3) hepatomegaly is best defined as an absolute increase of at least 1 cm in liver length at the midclavicular line; and if a baseline measurement is not available, hepatomegaly can be defined as greater than 2 SDs above normal for age; and (4) the presence and volume of ascites can be categorised as mild (minimal fluid by liver, spleen, or pelvis), moderate (<1 cm fluid), or severe (fluid in all three regions with >1 cm fluid in at least two regions).